Strategi Panti Pondok Lansia Al-Hikmah Berbasis Pesantren Dalam Upaya Mensejahterakan Lansia Di Desa Bendelonje Kecamatan Talun Kabupaten Blitar - Saputri , Rati Marleni; Choiriyah, Choiriyah; Isnaini , Mohd Aji (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Social institutions are at the forefront in carrying out the tasks and functions of implementing social welfare, especially the Al-Hikmah Islamic boarding school based boarding house in Bendelonje Village, Talun District, Blitar Regency. In general, there are many factors behind the entry of the elderly into the Al-Hikmah Elderly Home, consisting of various reasons. The Al-Hikmah boarding house for the elderly is really needed in providing solutions to the lives of abandoned elderly people so that their lives are more prosperous. Old age is a time for humans to live the remnants of a journey in life, namely by getting closer to Allah SWT. and multiply good deeds as a provision for the hereafter. This study aims to examine the strategies of the Al-Hikmah Islamic Boarding School for the elderly in an effort to prosper the elderly, including: strategies to build communication, strategies to provide basic needs, strategies to control security and protect the elderly, and strategies to provide elderly services. With the strategy provided by the Al-Hikmah Elderly Nursing Home it can be implemented properly and provide better welfare for the elderly.